KHARKIV CYCLING INFRASTRUCTURE DEVELOPMENT FEATURES - Sokolenko, Anna (Human Geography Journal, 2015)
The article focuses on cycling infrastructure development features in a number of European cities. The article outlines the main problems of a big city’s transport infrastructure and points out the advantages of a network of cycle paths and bike racks introduction to an urban space. Approach, based on the relevant researches analysis and successful experience of some western countries, substantiates creation of a full-fledged bicycle infrastructure in Kharkiv. By means of Delfi questionnaire citizent’s opinion concerning the question of creation and use of bicycle infrastructure is revealed; potential target audience is defined.